Expression of Ki67 in Precancerous Squamous Cell Skin Lesion of Mice Induced by DMBA - Siti Nurkasanah; Aida S D Hoemardani; Evlina Suzanna Sinuraya (National Cancer Center - Dharmais Cancer Hospital, 2019)
Background: Squamous cell carcinoma (SCC) is an invasive skin cancer that is found in the human skin. SCC growth from the precancerous lesion is known as a wart or papilloma. Ki67 is a protein expressed by cells during proliferation. Cells with higher Ki67 expression showed abnormal regulation of apoptosis. 5-FU is an antimetabolite compound that works as a DNA/RNA pyrimidine antagonist molecule that can induce cell apoptosis. The main objective of this research is to evaluate the inhibition proliferation of precancerous squamous cell in skin lesion induced by DMBA/croton oil treated by using 5-FU cream topically compared to 5% imiquimod cream. Methods: This research assesses three different concentrations of 5-FU cream namely 1%, 2%, and 5% topically on 24 wild type mice divided into 6 groups of 4 each including positive control (with carcinogenesis but without treatment), negative control (without treatment ; normal), carcinogenesis with treatment 5-FU cream (1%, 2%, and 5%) or 5% imiquimod cream. The expression of Ki67 was analyzed using immunohistochemistry. Statistical analysis was performed by one-way ANOVA using SPSS version 23. Results: Based on this research, 5-FU cream treatment during 4 weeks (week 10-week 14) showed the decrease of cumulative number of papilloma (p<0.05) and immunohistochemistry analysis resulted in the lowest Ki67 expression in 5-FU 2% and 5% groups compared to 5% imiquimod cream (p<0.05). Conclusions: 5-FU cream treatment during 4 weeks showed a decrease of papilloma and Ki67 expression in 5-FU cream 2% and